The Value of Trade Agreements in the presence of Political pressures - Maggi, Giovanni; Rodriguez‐Clare, Andres (Journal of Political Economy, 1998)
An argument often heard in favor of trade agreements is that, by committing to free trade, a government can credibly distance itself from domestic lobbies, But several existing models of endogenous protection suggest that governments have no interest in foreclosing interest group pressures since governments derive rents from the political process. We develop a small‐country model in which factors are sector‐specific in the short run but mobile in the long run. We show that in this setting a government may be worse off in the political equilibrium than under commitment to free trade, and hence it may value a trade agreement.